The sensitivity of TANDEM – A new measure of trauma competence - Rolf Gjestad; Dag Ø. Nordanger; Alina Coman; Anca Maria Yttri (PLoS ONE, 2026)
Background Despite international standards outlining the competence areas to be included in educational programs on trauma-informed care, a Norwegian expert group identified a lack of tools to measure the learning outcomes of such programs adapted to the Norwegian context. In response, they developed the Trauma and Development Education Monitor (TANDEM). This study examines the sensitivity of the instrument. Methods The study is based on pre- and post-test survey responses to TANDEM’s 55 items, covering the domains of Readiness, Agency, Reflexivity, Knowledge, Skills, and Work Culture, collected from 370 students across four cohorts enrolled in a three-week trauma course at Oslo Metropolitan University. Confirmatory factor analysis (CFA) with measurement invariance analyses were conducted to evaluate configural, weak, strong, and strict invariance in the reflective dimensions Readiness, Agency, and Reflexivity. Latent growth curve (LGC) models were then applied to analyze changes in outcome scores from pre- to post-program. Finally, LGC levels and changes in outcomes were predicted by participant background variables, i.e., workplace type, target age group, role type, work seniority, and prior trauma training. Findings TANDEM demonstrated sensitivity in detecting significant increases in scores from before to after the course, both for the instrument as a whole and across all domains, most notably for Knowledge and Skills. Some measurement invariance issues were identified in the Agency and Reflexivity domains, indicating interpretation problems. Significant pre–post changes for the total instrument were observed regardless of students’ workplace type, target age group and work seniority, but with greater improvements among those in non-problem focused role types and with less prior trauma training. Implications Overall, TANDEM shows promise as a tool for supporting the implementation, evaluation, and development of trauma competence programs in health and social care contexts. Future developments should test TANDEM across diverse educational, professional, and cultural groups, increase variance in the Readiness domain, refine and validate the domains, and validate the instrument against independent, performance-based competence measures.